Defining Strategic Management for Islamic Education Institution - Fanani, M Iffan; Sa’diyah, Maemunah; Ibdalsyah, Ibdalsyah; Tanjung, Hendri (International Journal of Islamic Thought and Humanities, 2024)
Strategic Management has attracted the interest of numerous experts and practitioners, as well as Islamic education experts and practitioners. In addition, they believe that strategic management may help Islamic educational institutions carry out their operations, hence it is assumed that strategic management is fully applied in Islamic educational institutions. This study seeks to investigate and clarify the notion of strategic management in the context of Islamic educational institutions. This study concludes that the (conventional) strategic management concept cannot be fully implemented in Islamic educational institutions because the conventional strategic management concept is constructed within a business context, emphasizing the significance of competitiveness and obtaining returns above the average competitor. This study provides a new concept of strategic Islamic management for Islamic educational institutions, based on the premise that collaboration is more fundamental than competition, and that maintaining organizational sustainability and the quality of education given requires excellence (ihsan).